Groover's Principles of Modern Manufacturing: Materials, Processes, and Systems - Groover, Mikell P. (New Delhi John Wiley & Sons Ltd, 2013)
Engineers rely on Groover because of the book's quantitative and engineering-oriented approach that provides more equations and numerical problem exercises. The fourth edition introduces more modern topics, including new materials, processes and systems. End of chapter problems are also thoroughly revised to make the material more relevant. Several figures have been enhanced to significantly improve the quality of artwork. All of these changes will help engineers better understand the topic and how to apply it in the field.
International Edition.